2020
DOI: 10.1515/hmbci-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of amylase and lipase levels on pancreas injury diagnosis in patients with blunt abdominal trauma

Abstract: ObjectivesDespite the low incidence of pancreatic injury in the abdominal blunt trauma (BTA), its early diagnosis is very important; since pancreatic injury is associated with high rates of morbidity and mortality. However, due to the high association of pancreatic injury with injury of other abdominal organs, its diagnosis may be delayed and complicated. The use of imaging modalities is also subject to limitations for reasons such as cost, unavailability, and harmfulness. Consequently, the present study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
2
0
3
Order By: Relevance
“…Different studies reported that COVID-19-induced PI is diagnosed through detailed medical history, physical examination, and ultrasonography imaging with elevation in serum lipase levels. However, in severe cases, abdominal CT scan imaging is recommended (25). In COVID-19, PI may occur either by direct invasion of SARS-CoV-2 or indirectly through the induction of CS (26).…”
Section: Covid-19 and Pancreatic Injurymentioning
confidence: 99%
“…Different studies reported that COVID-19-induced PI is diagnosed through detailed medical history, physical examination, and ultrasonography imaging with elevation in serum lipase levels. However, in severe cases, abdominal CT scan imaging is recommended (25). In COVID-19, PI may occur either by direct invasion of SARS-CoV-2 or indirectly through the induction of CS (26).…”
Section: Covid-19 and Pancreatic Injurymentioning
confidence: 99%
“…Esto concuerda con un estudio de 134 pacientes, 43 (32 %) presentaban lesión esplénica, 28 (20.8 %) hepática, 6 (4.4 %) lesiones intestinales, de los cuales 4 (2.9 %) correspondían a intestino delgado y 2 (1.4 %) al intestino grueso (Parra-Romero et al, 2019) (Rao et al, 2018). Hay autores que sugieren que después del bazo y el hígado se afectan en mayor frecuencia los riñones, seguidos del páncreas (Hosseininejad et al, 2020). Otros estudios que comparten la idea que la lesión renal posee mayor frecuencia por sobre la intestinal (He et al, 2020) (Belman & Toka, 2019.…”
Section: óRganos Afectadosunclassified
“…Existe debate sobre la validez de las concentraciones de amilasa y lipasa en el contexto de trauma abdominal contuso. Si bien es cierto, puede existir niveles elevados de estas enzimas en lesiones de lengua, esófago, duodeno, intestino delgado, hígado, hemorragia intracraneal o pacientes críticos en unidades de terapia intensiva; existen estudios que demuestran su valor en detectar el trauma pancreático agudo (Hosseininejad et al, 2020).…”
Section: Amilasa Y Lipasaunclassified
“…Esto concuerda con un estudio de 134 pacientes, 43 (32 %) presentaban lesión esplénica, 28 (20.8 %) hepática, 6 (4.4 %) lesiones intestinales, de los cuales 4 (2.9 %) correspondían a intestino delgado y 2 (1.4 %) al intestino grueso (Parra-Romero et al, 2019) (Rao et al, 2018). Hay autores que sugieren que después del bazo y el hígado se afectan en mayor frecuencia los riñones, seguidos del páncreas (Hosseininejad et al, 2020). Otros estudios que comparten la idea que la lesión renal posee mayor frecuencia por sobre la intestinal (He et al, 2020) (Belman & Toka, 2019).…”
Section: óRganos Afectadosunclassified